Phytocoenotic Features of Caragana scythica (Kom.) Pojark. (Fabaceae Lindl.) in the Donetsko-Priazovsky region (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
Phytocoenotic features of the relictual endemic Caragana scythica (Kom.) Pojark. (Fabaceae Lindl.) in the Donetsko-Priazovsky region is studied. Ecotopic and phytocoenotic characteristics of 32 localities is given. Core species of the phytocoenoses under consideration are distinguished, phytocoenotic connections of the species are also revealed and analyzed. Basing on positive association with C. scythica, the species Festuca valesiaca Gaudin, Galatella villosa Rchb. f., Bromopsis riparia (Rehmann) Holub, Salvia nutans L., Euphorbia seguieriana Neck. have been pointed out as a floristic complex, i.e. a biomarker of probable habitats for this species.
Keywords: relictual endemic, phytocoenotic characteristics, floristic complex – a biomarker of habitats, the Donetsko-Priazovsky region.